The Design of A Multi-Skills Appliance and Its Effect to Improve the Sum of Motor, Functional Abilities and Skills of Passing and Scoring for Female Students in the Futsal - Mohammed Naji Shaker Abugneam (Journal of Global Pharma Technology, 2017)
Futsal is one of the basic lessons for female students in the College of Physical Education and SportsSciences in the first stage of study in Iraq, for the purpose of learning the basic skills in this game andsome functional and motor abilities and quickly, the researchers designed a multi-skills appliance thathelps in learning a number of skills including scoring, passing, quitting and rolling ball. The multi-skillsappliance consists of three parts, each measuring 2 meters, can be connected to each other according toneed and variety of skill. The exercises used on the appliance designed to improve the performance of theexperimental group compared to the control group according to the statistical results of the tests, wherethe allotted time was 90 minutes distributed on the three parts of the preparatory and main and finalcourses. The number of learning units for passing and scoring was two units per week for 6 weeks, with atotal of 12 units.Keywords: Skills, Educational appliance design, Futsal, Motor accuracy, Scoring, Motorlearning, Anaerobic ability and passing.